Meningkatkan Fokus Peserta Didik Terhadap Pembelajaran PAI Dengan Menggunakan Metode Think Pair Share - Rahmah, Siti Nurul; Sakinah; Rachmawati; Aini, Nur Aini Farida; Makbul, M. Makbul (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
The study aims to find out how to improve the focus of students in learning Islamic Religious Education (PAI) using the Think Pair Share (TPS) method at class V Sukaharja II Karawang State Elementary School. This type of research is class action research (PTK). The subject of this study is a student of the V class of 34 people, the object of this research is to increase the focus on the student in PAI examination using the Think Pair Share (TPS) method, the implementation of learning carried out through the activities of visiting the research instrument namely observation sheets and lifts. From the data analysis of learning methods Think Pair Share can improve the focus of learning on PAI learning in grade V SD State Sukaharja II Karawang. The increase in students focusing on learning from cycle I to cycle II is about 60 % to 94 %.